Reliving the rape of Tamar: Absolom's revenge in 2 Samuel 13 - Rudman, Dominic (Old Testament essays, 1998)
This article considers the rape of Tamar as prologue to the revenge of Absalom on the perpetrator in 2 Samuel 13. This revenge is, in effect, a replaying of the circumstances surrounding the rape but with Amnon as the victim. Absalom breaks the same ties of kinship and hospitality as his brother, a parallel which is heightened by the central role played by David as unwitting dupe in placing both Tamar and then Amnon at the mercy of their would-be attackers.